NANOTECHNOLOGY – THE BRAINCHILD OF MODERN FUNDAMENTAL SCIENCE - Геник, С. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Nanotechnology is an industry which takes place between fundamental and applied science and technology. it provides the ability to create and modify the objects that include smaller than 100 nanometers in one or more planes. These components get the innovative qualities that allow them to commit integration into the complete systems on a larger scale. Considering of the human body as a system of interlocking networks, using the nanotechnology for detection of damage which arise in them, nanotechnology produces completely new approaches to finding the causes of various diseases, their treatment and even prevention.